“Am I Being Rude”: Exploring Indonesian Students’ Intercultural Communicative Competence in Inner Circle Countries - Yuzar, Ella (Lingual Journal of Language and Culture; Vol 13 No 1 (2022): Lingual: Journal of Language and CultureDO - 10.24843/LJLC.2022.v13.i01.p02, 2022)
Studies in Intercultural Communication Competence (ICC) has been extensively investigated by numerous experts in the last decade. Some models and approaches have been constructed to the purposes of developing individuals’ competency in intercultural communication context. However, some problems occurred due to cultural discrepancy. The purpose of this study is to explore strategies being used by Indonesian postgraduates’ students to be inter-culturally and communicatively competent. Interviews session (adopted from Fantini’s conceptual framework) with sixteen Indonesian students have been conducted to scrutinise their personal experienced and awareness in intercultural communication setting. Despite the fact that the existences of cultural diversity in inner circle countries, Indonesian students have attempted to exposure more in intercultural interaction. They converged themselves with other international students as well as with locals in the community. From a critical perspective, this study suggested that Indonesian students should attempt to shift out from their ‘very own’ circle. Equally significant, to be more open to initiate more deep conversation and involve in a more interactive, intercultural communication settings, with other students from different countries.